2015 IEEE Conference on Control Applications (CCA) 2015
DOI: 10.1109/cca.2015.7320809
|View full text |Cite
|
Sign up to set email alerts
|

L<inf>1</inf> analysis of LTI systems via piecewise higher-order approximation

Abstract: This paper deals with the L1 analysis of linear time-invariant (LTI) systems, by which we mean the L∞-induced norm analysis of LTI systems. It is well known that this induced norm corresponds to the L1 norm of the impulse response of the given system, i.e., integral of the absolute value of the kernel function in the convolution formula for the input/output relation. However, because it is very hard to compute this integral exactly or even approximately with explicit upper and lower bounds, the ideas of piecew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Very importantly, the improvement over our earlier studies [19], [20] is not limited simply to the use of such higher order approximation schemes (and establishing theoretical bases for these schemes) but includes generalized arguments relevant to how the Taylor expansion of relevant functions is used; even though the earlier studies only considered the Taylor expansion at the beginning of each subintervals resulting from the application of fast-lifting, this paper considers taking advantage of the freedom in the time instant around which relevant functions are expanded to Taylor series. In this respect, this paper corresponds to a significantly extended version of an earlier conference paper by the authors [22], which discussed the development of the piecewise quadratic and cubic approximation schemes for the first time (without associated proofs and numerical examples). Under such generalized treatment, it is once again shown that the kernel approximation approach is quantitatively superior to the input approximation approach in terms of the gap between the upper and lower bounds, even though the convergence rate itself (as mentioned above) is shared by the two approaches under the same approximation order.…”
Section: A Related Studies On the L∞-induced Norm Analysismentioning
confidence: 99%
“…Very importantly, the improvement over our earlier studies [19], [20] is not limited simply to the use of such higher order approximation schemes (and establishing theoretical bases for these schemes) but includes generalized arguments relevant to how the Taylor expansion of relevant functions is used; even though the earlier studies only considered the Taylor expansion at the beginning of each subintervals resulting from the application of fast-lifting, this paper considers taking advantage of the freedom in the time instant around which relevant functions are expanded to Taylor series. In this respect, this paper corresponds to a significantly extended version of an earlier conference paper by the authors [22], which discussed the development of the piecewise quadratic and cubic approximation schemes for the first time (without associated proofs and numerical examples). Under such generalized treatment, it is once again shown that the kernel approximation approach is quantitatively superior to the input approximation approach in terms of the gap between the upper and lower bounds, even though the convergence rate itself (as mentioned above) is shared by the two approaches under the same approximation order.…”
Section: A Related Studies On the L∞-induced Norm Analysismentioning
confidence: 99%